TEACHING METHODOLOGY OF DRAWING BASED ON THE COMPETENCY-BASED APPROACH - Eshmurodov Axmadjon Nurmuradovich (O‘RTA OSIYODA IJTIMOIY VA GUMANITAR TADQIQOTLAR, 2025)
Annotation: This article examines the methodology of teaching the subject of drawing (technical graphics) through a competency-based approach. The study focuses on how to develop students’ professional and creative competencies by integrating theoretical knowledge with practical skills. The author highlights the pedagogical principles, teaching strategies, and technological tools that enhance the effectiveness of drawing lessons. Emphasis is placed on forming students’ spatial thinking, graphic literacy, and design culture as essential competencies for future professionals. The article also explores the alignment of competency-based learning outcomes with modern educational standards and lifelong learning objectives.